Perancangan Sistem Informasi Inventori Gudang Berbasis Intranet - Iryaning, Dwi (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
PT Duta Mas Satu Pasuruan which be active in area produce of plywood, in activity documentation of data relating with inventory product still be done in a manual so that the problem which often faced was report access inventory limited to space and time where sales department didn’t know number supply of product in warehouse because doesn’t have information access connected. Arrangement of good inventory must always can answer question how much the product available in warehouse and when the product is required. So, for know the product stock especially product become then required by Information Inventory Warehouse System (SIGA) bases on Intranet. This implementation used scripting language discharged at HTML for enables checking and supervision directly through computer tissue system. Information Inventory Warehouse System (SIGA) made with software open source using program language of PHP and management of data base MySQL, and then used server computer bases on Windows. Information data of stock product which is available in warehouse has 4 kinds of product type, there are DF (4' × 8') 15000 slabs, MDF component design 18000 slabs, Plywood 24000 slabs and Fancywood 9000 slabs.